أثر الألعاب الشبه رياضية في تحسين بعض مؤشرات الصحة النفسية - ‫حفصي‬‫ عيسى‬; خميسي مطرفي (My University, 2025)
‫تهدف‬‫هذه‬ ‫الدراسة‬ ‫للكشف‬ ‫عن‬ ‫مدى‬ ‫مساهمة‬ ‫األلعاب‬ ‫الحركية‬ ‫في‬ ‫اكتساب‬ ‫بعض‬ ‫المؤشرات‬ ‫الصحة‬‫النفسية‬ ‫والوقوف‬ ‫على‬ ‫أهم‬ ‫التحديات‬ ‫والمعيقات‬ ‫التي‬ ‫تقف‬ ‫عائقا‬ ‫أمام‬ ‫األساتذ‬ ‫ة‬‫في‬ ‫اكتساب‬ ‫األطفال‬‫المؤشرات‬ ‫الصحة‬ ‫النفسية‬ ‫‪،‬‬‫وذلك‬ ‫من‬ ‫خالل‬ ‫اإلجابة‬ ‫على‬ ‫التساؤالت‬ ‫التالية‪:‬‬ ‫اإلشكالية‬‫الرئيسية‪:‬‬ ‫‪-‬‬‫هل‬ ‫األلعاب‬ ‫الحركية‬ ‫لها‬ ‫دور‬ ‫في‬ ‫اكتساب‬ ‫بعض‬ ‫مؤشرات‬ ‫الصحة‬ ‫النفسية‬ ‫لدى‬ ‫تالميذ‬ ‫التعليم‬ ‫االبتدائي‬‫من‬ ‫وجهة‬ ‫نظر‬ ‫أساتذة‬ ‫التربية‬ ‫البدنية‬ ‫؟‬ ‫ولقد‬‫دعمنا‬ ‫هذه‬ ‫اإل‬ ‫شكالية‬‫بطرح‬ ‫التساؤ‬ ‫الت‬‫الفرعية‬ ‫التالية‪:‬‬ ‫األسئلة‬‫الفرعية‬ ‫‪:‬‬ ‫‪-‬‬‫هل‬‫األلعاب‬ ‫الحركية‬ ‫لها‬ ‫دور‬ ‫في‬ ‫تحسين‬ ‫التكيف‬ ‫اإلجتماعي‬ ‫لدى‬ ‫تالميذ‬ ‫التعليم‬ ‫االبتدائي‬ ‫من‬ ‫وجهة‬ ‫نظر‬‫أساتذة‬ ‫التربية‬ ‫البدنية‬ ‫؟‬ ‫‪-‬‬‫هل‬‫األلعاب‬ ‫الحركية‬ ‫لها‬ ‫دور‬ ‫في‬ ‫تحسين‬ ‫الثقة‬ ‫بالنفس‬ ‫والقدرة‬ ‫على‬ ‫التعبير‬ ‫لدى‬ ‫تالميذ‬ ‫التعليم‬ ‫االبتدائي‬‫من‬ ‫وجهة‬ ‫نظر‬ ‫أساتذة‬ ‫التربية‬ ‫البدنية‬ ‫؟‬ ‫ولإلجابة‬‫عليها‬ ‫قمنا‬ ‫بإجراء‬ ‫دراسة‬ ‫على‬ ‫مستوى‬ ‫ابتدائبة‬ ‫بمدينة‬ ‫تيارت‬ ‫في‬ ‫الفترة‬ ‫الممتدة‬ ‫بين‬ ‫‪26‬‬ ‫أفريل‬‫إلى‬ ‫‪25‬‬ ‫ماي‬ ‫‪2025‬‬ ‫مستخدمين‬ ‫الم‬ ‫نهج‬‫الوصفي‬ ‫التحليلي‬ ‫‪،‬‬‫وباستعمال‬ ‫تقنية‬ ‫أداة‬ ‫االستبيان‬ ‫للتعرف‬‫على‬ ‫مدى‬ ‫مساهمة‬ ‫األل‬ ‫عاب‬‫الحركية‬ ‫في‬ ‫اكتساب‬ ‫بعض‬ ‫مؤشرات‬ ‫الصحة‬ ‫النفسية‬ ‫من‬ ‫خالل‬ ‫التوجه‬‫باالستبيان‬ ‫لألساتذة‬ ‫في‬ ‫بلدية‬ ‫زمالة‬ ‫عبد‬ ‫القادر‬ ‫التي‬ ‫وزعناها‬ ‫ل‬ ‫‪50‬‬ ‫أستاذ‬ ‫‪،‬‬‫وهذا‬ ‫من‬ ‫أجل‬ ‫التعرف‬‫على‬ ‫واقع‬ ‫األلعاب‬ ‫الحركية‬ ‫داخل‬ ‫المدرسة‬ ‫لإلجابة‬ ‫على‬ ‫أسئلة‬ ‫االستمارة‬ ‫لنستخلص‬ ‫في‬ ‫األخير‬‫النتائج‬ ‫التالية‪:‬‬ ‫‪-‬‬‫أ‬‫ن‬‫ا‬ ‫أللعاب‬‫الحركية‬ ‫تساعد‬ ‫التلميذ‬ ‫على‬ ‫الشعور‬ ‫بالكفاءة‬ ‫والقدرة‬ ‫على‬ ‫النجاح‬ ‫في‬ ‫األنشطة‬ ‫‪.‬‬ ‫هذا‬ ‫الشعور‬‫باإلنجاز‬ ‫والقدرة‬ ‫يعزز‬ ‫بشكل‬ ‫كبير‬ ‫من‬ ‫قيمة‬ ‫الذات‬ ‫لدى‬ ‫التلميذ‬ ‫ويقلل‬ ‫من‬ ‫مشاعر‬ ‫عدم‬ ‫الكفاءة‬‫التي‬ ‫قد‬ ‫تؤثر‬ ‫سلبًا‬ ‫على‬ ‫الصحة‬ ‫النفسية‬ ‫‪.‬‬
This study aims to reveal the extent to which motor games contribute to acquiring some mental health indicators and to identify the most important challenges and obstacles that stand in the way of teachers in children acquiring mental health indicators, by answering the following questions: Main problem: Do motor games have a role in the acquisition of some indicators of mental health in primary education students from the perspective of physical education teachers? We supported this problem by asking the following sub-questions: Sub-questions: Do motor games play a role in improving social adaptation among primary education students from the point of view of physical education teachers? Do motor games have a role in improving self-confidence and the ability to express in primary education students from the point of view of physical education teachers? To answer them, we conducted a study at the primary level in the city of Tiaret in the period from April 26 to May 25, 2025, using the descriptive analytical approach, and using the questionnaire tool technology to identify the extent to which motor games contribute to the acquisition of some mental health indicators by directing the questionnaire to professors in the municipality of Zamala Abdelkader, which We distributed it to 50 professors This is in order to learn about the reality of action games within the school in order to answer the questions of the form, so that we can finally draw the following result That motor games help the pupil to feel competent and able to succeed in activities. This sense of accomplishment and ability greatly enhances the pupil's self-worth and reduces feelings of inadequacy that may negatively affect psychological well-being